Coeliac disease in monozygotic twins. Issue 686 (December 1982) - Shale, Dennis J.; Hall, Reginald; Johnston, Desmond G.; Roberts, D. F.
Abstract : A case of concordance for coeliac disease in monozygous twins is reported. One presented with failure to enter puberty and responded to the exclusion of gluten from her diet. The other twin was asymptomatic. They represent a well documented example of monozygous twins with concordance for coeliac disease.